Health, lifestyle and occupational risks in Information Technology workers. (30th January 2021) - Lalloo, D; Lewsey, J; Katikireddi, S V; Macdonald, E B; Demou, E
Abstract: Background: Information technology (IT) and the IT workforce are rapidly expanding with potential occupational health implications. But to date, IT worker health is under-studied and large-scale studies are lacking. Aims: To investigate health, lifestyle and occupational risk factors of IT workers. Methods: We evaluated self-reported health, lifestyle and occupational risk factors for IT workers in the UK Biobank database. Using logistic regression, we investigated differences between IT workers and all other employed participants. Regression models were repeated for IT worker subgroups (managers, professionals, technicians) and their respective counterparts within the same Standard Occupational Classification (SOC) major group (functional managers, science and technology professionals, science and technology associate professionals). Results: Overall, 10 931 (4%) employed participants were IT workers. Compared to all other employed participants, IT workers reported similar overall health, but lower lifestyle risk factors for smoking and obesity. Sedentary work was a substantially higher occupational exposure risk for IT workers compared to all other employed participants (odds ratio [OR] = 5.14, 95% confidence interval [CI]: 4.91–5.39) and their specific SOC group counterparts (managers: OR = 1.83, 95% CI: 1.68–1.99, professionals: OR = 7.18, 95% CI: 6.58–7.82, technicians: OR = 4.48, 95% CI: 3.87–5.17). IT workers were also more likely to engage in computer screen-time outside work than all other employed participants (OR = 1.42, 95% CI: 1.35–1.51). Conclusions: Improved understanding of health, lifestyle and occupational risk factors from this, the largest to date study of IT worker health, can help inform workplace interventions to mitigate risk, improve health and increase the work participation of this increasingly important and rapidly growing occupational group.